Choosing the place of birth: All European, all equal? [in Portuguese] - Santos, M. (ENCA / Nascer em Amor, 2017)
Regarding childbirth, what makes us all European? To a certain degree, we all share values, principles and norms. But big differences arise in respect to the options available and the limitations to free and informed choices. In this presentation, I aim to stir the debate on the place of birth by mapping some of the differences and similarities across Europe.